Immunohistochemical expression of HOXA1, and Ki-67 proteins of oral squamous cell carcinoma - Ibtehal Q Al-Etbi; Riyadh O Al-Kaisi (College of Dentistry/ University of Baghdad, 2014)
Background: Oral squamous cell carcinoma (OSCC) is the most prevalent malignant neoplasm of the oral cavity and constitutes a major health problem in developing. In the last 30 years, the 5-year survival rate of patients with oral SCC has not improved despite advance in diagnostic techniques. To improve early diagnosis for this deadly disease, new biological markers are needed. HOX genes encode homeodomain-containing transcription factors involved in the regulation of cellular proliferation and differentiation during embryogenesis. HOX gene expression has been described in several adult tissues, where they performed important roles in maintaining homeostasis. Few studies have suggested that HOXA1 plays a role in tumorigenesis. Besides being overexpressed in several tumors, HOXA1 influences numerous cellular processes including proliferation, apoptosis and epithelialmesenchymal transition (EMT), and HOXA1 overexpression is sufficient for malignant transformation ofnontumorigenic epithelial cells. Ki-67 is a specific marker of proliferation and the expression of which is strictly associated with cell proliferation and is widely used in pathology as a proliferation marker to measure the growth fraction of cells in human tumors.The aims of this study were to evaluate the immunohistochemical expression of HOXA1 & Ki-67 in OSCC & to correlate the expression of the studied markers with the clinicopathological findings and with each other Materials and Methods: Thirty formalin-fixed, paraffin- embedded tissue blocks of oral squamous cell carcinoma were included in this study. H&E stain was done for each block for reassessment of histological examination. An immunohistochimical stain was performed using anti HOXA1 and anti Ki-67 poly clonal antibodies. Results:The expression of HOXA1 and Ki-67were positive in all oral squamous cell carcinoma cases & in all layers (100%), while the expression was restricted to the basal and supra basal layer in normal oral mucosa. Statistically non-significant correlation observed between each marker with clinico-pathological parameters. While a statistically significant association was found between the expressions of two markers, (p-value= 0.027). Conclusion: The statistically significant association observed between expressions of HOXA1 with the specific marker of proliferation Ki-67. This suggested important role in oral SCC development and progression.